2002
DOI: 10.1080/08035250252834030
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of drugs in Italy: a prospective, observational and multicentre study

Abstract: Despite prescription profile differences among centres, off-label use was high everywhere. Immediate action for more rational drug use is necessary and requires not only regulatory intervention but also a more evidence-based, therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 22 publications
6
33
1
6
Order By: Relevance
“…Observing the profile of oral solutions and suspensions compounded for newborns and children of the studied hospital, it was verified that solutions/suspensions of these active principles were identified in other studies: folic acid,9 , 19 folinic acid,9 , 20 ursodeoxycholic acid,11 , 14 captopril,8 , 9 , 14 , 15 , 18 , 21 caffeine,12 , 16 , 19 , 22 , 23 spironolactone,9 , 24 - 28 fluconazole,17 furosemide,8 , 9 , 26 hydrochlorothiazide,8 , 9 , 18 , 26 , 27 propranolol,10 ranitidine,9 pyrimethamine17 and sulfadiazine 17. Therefore, it is observed that the demand for oral solutions and suspensions administered to newborns and children in this study has also been observed in other studies and that the compounding of drugs is a national and international necessity due to the lack of oral liquid drugs from the pharmaceutical industry.…”
Section: Discussionsupporting
confidence: 66%
“…Observing the profile of oral solutions and suspensions compounded for newborns and children of the studied hospital, it was verified that solutions/suspensions of these active principles were identified in other studies: folic acid,9 , 19 folinic acid,9 , 20 ursodeoxycholic acid,11 , 14 captopril,8 , 9 , 14 , 15 , 18 , 21 caffeine,12 , 16 , 19 , 22 , 23 spironolactone,9 , 24 - 28 fluconazole,17 furosemide,8 , 9 , 26 hydrochlorothiazide,8 , 9 , 18 , 26 , 27 propranolol,10 ranitidine,9 pyrimethamine17 and sulfadiazine 17. Therefore, it is observed that the demand for oral solutions and suspensions administered to newborns and children in this study has also been observed in other studies and that the compounding of drugs is a national and international necessity due to the lack of oral liquid drugs from the pharmaceutical industry.…”
Section: Discussionsupporting
confidence: 66%
“…This finding reinforces the need for an adequate pharmaceutical form of medicinal products for the paediatric population since formulations suitable for the paediatric population are often unavailable, and therefore, licenced drugs have to be modified into extemporaneous preparations with unknown pharmacokinetic characteristics [2,56,57]. It was, however, possible to establish that the ATC groups which were most prescribed on an off-label and/or unlicenced basis were systemic hormonal preparations, excluding sex hormones and insulins (H), with some studies specifically identifying betamethasone and beclomethasone [21,23] and dexamethasone [36,42], i.e. the active substances in this group.…”
Section: 5mentioning
confidence: 99%
“…Clinicians are therefore forced to extrapolate study data from adults. As a consequence, many drugs used in paediatric patients are prescribed without full knowledge on the optimal dosage and potential adverse drug reactions [1,2].…”
Section: Introductionmentioning
confidence: 99%